A Review of The Suitability of Mangrove Agro-ecotourism Areas in Perupuk Village, Batubara Regency, North Sumatra Province - Uswatul Hasan; Siti Mardiana; Syahbudin Hasibuan (Universitas Labuhanbatu, 2024)
This study aimed to measure the suitability of mangrove ecosystems in Perupuk village, Batubara district as an ecotourism area. Several ecological parameters were used as a basis for considering suitability including mangrove type, thickness, and density. In addition, biota diversity and tidal height were also observed. Mangrove observations were carried out using the 10 x 10 metre quadratic transect method as many as 20 pieces were let on the shoreline area toward, land. The results showed that this area was only overgrown with Avicennia marina with a thickness of 203.7 meters, and a density of 2100 Ind/ha. There are 31 species of biota associated with mangrove ecosystems consisting of 3 bivalve species, 1 gastropod, 6 fish, 16 birds, 2 crustaceans, 2 arthropods, and 1 mammal. The results of the ecotourism suitability index analysis show that this area is very suitable for mangrove ecotourism sites with a suitability value of 73.75%